Analysis of Indonesian Public Health Factors 2023 with PCA Method and Factor Analysis - Wulandari, Sri; Sari, Nadifa; Imani, Revina (Indonesian Journal Publisher, 2025)
Indonesia is a developing country with a high population, which faces great challenges in maintaining public health, especially in the era of accelerating globalization. Public health is an important issue in the face of urbanization, economic growth, and increasing demand for livelihoods. This challenge requires not only the provision of medical services but also equitable access for the entire community, including those living in remote areas or with economic limitations. Based on Susenas 2023 data, around 26% of Indonesia's population experienced health complaints in the past month, although the Graph has decreased from 29.94% in the previous year. This study aims to identify factors that affect public health in each province in Indonesia, using the main component analysis (PCA) method and factor analysis. The research data comes from the Central Statistics Agency (BPS) with six variables, namely life expectancy, exclusive breastfeeding in infants <6 months, poverty percentage, prevalence of food inadequacy, number of medical personnel, and poverty depth index. Data processing is carried out with SPSS, the results are presented in boxplots and tables for easy decision-making. The results of the study show that most of the data characteristics, namely data tend to have great diversity and the data has met the normal assumption of multivariation, dependent data, data adequacy, and correlation between significant variables. In addition, two main factors that are formed in affecting public health are socio-economic conditions and food security.